2011
DOI: 10.1073/pnas.1018109108
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulatory and repressive inputs localize Hydra Wnt3 to the head organizer

Abstract: Polarized Wnt signaling along the primary body axis is a conserved property of axial patterning in bilaterians and prebilaterians, and depends on localized sources of Wnt ligands. However, the mechanisms governing the localized Wnt expression that emerged early in evolution are poorly understood. Here we find in the cnidarian Hydra that two functionally distinct cis-regulatory elements control the head organizer-associated Hydra Wnt3 (HyWnt3). An autoregulatory element, which mediates direct inputs of Wnt/ β-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
177
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(202 citation statements)
references
References 45 publications
13
177
2
Order By: Relevance
“…In line with these new hypotheses, we found that Wnt signaling can also be effectively suppressed at the transcriptional level (Nakamura et al 2011). The removal of a repressor element in the regulatory region of Wnt3 resulted in an expansion of the Wnt3 gene expression domain toward the gastric region (Fig.…”
Section: Local Restriction Of the Organizersupporting
confidence: 60%
See 2 more Smart Citations
“…In line with these new hypotheses, we found that Wnt signaling can also be effectively suppressed at the transcriptional level (Nakamura et al 2011). The removal of a repressor element in the regulatory region of Wnt3 resulted in an expansion of the Wnt3 gene expression domain toward the gastric region (Fig.…”
Section: Local Restriction Of the Organizersupporting
confidence: 60%
“…These two Wnt clusters are also supported by recent molecular phylogenies on Wnt genes (Cho et al 2010;Janssen et al 2010). How the interacting Wnt ligands are regulated is rather unknown so far, but it is tempting to speculate that there is a regulative hierarchy of Wnt gene expression similar to that described for Hydra (Nakamura et al 2011) or Drosophila (van de Wetering et al 1997Lessing and Nusse 1998).…”
Section: Synteny and Evolution Of Wnt Genesmentioning
confidence: 65%
See 1 more Smart Citation
“…As a result of caspase activation, signaling molecules as Wnt3 are transiently release leading to the activation of β-catenin signaling in the surrounding cycling progenitors followed by their mitotic division (not depicted here, see in (Chera et al 2009b;Galliot and Chera 2010). A couple of hours after bisection a series of early genes are upregulated in the endodermal epithelial cells, including the Wnt3 gene that contains CREs in its regulatory sequences (Gauchat et al 1998;Technau and Bode 1999;Hobmayer et al 2000;Kaloulis et al 2004;Chera et al 2007;Chera et al 2009b;Chera et al 2011;Lengfeld et al 2009;Nakamura et al 2011). By contrast after decapitation (80% body length) head injuryinduced apoptosis and apoptosis-induced compensatory proliferation are not observed (Galliot and Chera 2010) and Wnt3 seems to be directly upregulated in the epithelial cells (Lengfeld et al 2009).…”
Section: % Inhibited After Decapitationmentioning
confidence: 99%
“…Similarly RSK, CREB and CBP require a functional pathway to maintain their level of expression and their head-regeneraiton specific upregulation (Chera et al 2011). The recent functional dissection of the regulatory sequences of Wnt3 identified an autoregulatory element as well as a repressor element that restricts Wnt3 expression to the organizer region but also binding sites for CREB (Nakamura et al 2011). Therefore, beside their participation in injury-induced apoptosis in the interstitial cells, RSK, CREB and CBP also likely play in the epithelial cells a key role to modulate the expression of the early head regeneration genes that are essential for the establishment of the head organizer ( Figure 5).…”
Section: Early Genes In the Head Organizer And Putative Regulation Bymentioning
confidence: 99%